Fato e opinião nas avaliações do SPAECE – a perspectiva das sequências textuais - Leal, Francisca Verônica de Carvalho (2023)
The research, with a propositional and qualitative basis, aims to propose activities that favor the process of appropriating the understanding of argumentative strategies in the official test applied in the public network SPAECE (Permanent System of Evaluation of Basic Education of Ceará), by students of the 9th grade, focusing especially on Knowledge 6 (Distinguishing fact from opinion relative to fact) because it presents a gap in the learning revealed in the reports of the SPAECE applications. This work is based on the theoretical assumptions of Text Linguistics and, more specifically, anchored in Cavalcante et al. (2022) when stating that all texts are organized and structured to carry out communicative acts. And by theorists Adam (2019), who proposes five textual sequences: narrative, descriptive, explanatory, argumentative and dialogic, but in this research the discussion aims around the narrative and argumentative sequence; and by Perelman and Olbrechts-Tyteca (1996), who defend as the objective of argumentation theory, persuading the listener and convince him of the proposed thesis. This research consists of a notebook of activities proposed for 9th grade students, whose objective is to give them the opportunity to reflect on the conscious distinction of Knowledge 6 (Distinguishing fact from opinion relative to fact), which can be consolidated when students are qualified to go through the notebook of proposed activities.